Professores de salas de recursos multifuncionais: vivências de prazer e sofrimento no contexto de trabalho - Macedo, Edilson Barros de (Universidade Federal do Tocantins, 2018)
In Brazil, the construction of public policies aimed at people with special educational needs began at the end of the nineteenth century, a period in which, based on European experiences, the first institutions were created with the purpose of attending to those who at the time had some deficiency auditory, visual and physical. It was only in the 50s and 60s that truly began the construction of more contemplative services and consistent with the needs of the Brazilian population. Thus, there is the so-called specialized educational service that among its several services exists the multifunctional resource room, a space located in the school where the specialized educational service is offered to students with special educational needs. In this context, the present research, of a qualitative, exploratory and descriptive nature, aimed to identify the main experiences of pleasure and suffering of teachers working in multipurpose resource rooms in the city of Colinas Tocantins. In order to do so, it was applied to seven teachers working in these rooms, a semi-structured interview that had its results analyzed using Bardin's content analysis technique (1977/2011) via content analysis in stages described by Moraes (1999), with theoretical foundation of work psychodynamics. It was concluded that the teacher of the multifunctional resource room, depending on the subjective mobilization against the suffering that is inherent in work, could experience pleasure or the so-called pathogenic suffering. In this way, the teacher will be subjected to experiences of suffering when he is inserted in negligent work spaces for his subjective questions, inflexible in his prescriptions of work and organizational process, thus avoiding the transformation of the so-called prescribed work into actual work. On the other hand, the teaching worker will experience pleasure when, as a result of his coping strategies, he is able to transform the contextual reality of the work organization, from then on, carrying out work with meanings for himself and for the social environment and having acceptance, recognition and appreciation through the institution and society in general. It is suggested the construction of strategies and public policies with the objective of promoting closer relations between the teacher of the multifunctional resource room and the institutional, social and family community so that all have an adequate understanding of the educational activities carried out and the importance socially marginalized people and within the family itself, in their needs and potentialities.